Adapting Television Drama - Hogg, Christopher. author. aut Link
XI, 263 p. 1 illus.
Keywords: This book explores adaptation in its various forms in contemporary television drama. It considers the mechanics of adaptation as an ever-more prevalent form of production, most notably in the reworking of literary sources for television. It also explores the broader process through which the television industry as a whole is currently making necessary adaptations in how it tells stories, especially in relation to important concerns of equality, diversity and inclusion. Offering and analysing 16 original interviews with leading British television producers, writers, directors, production designers, casting directors and actors, and with a particular focus on female and/or minority-ethnic industry perspectives, the book examines some of the key professional and creative approaches behind television adaptations today. The book connects these industry insights to the existing conceptual and critical frameworks of television studies and adaptation studies, illuminating the unique characteristics of television adaptation as a material mode of production, and revealing television itself as an inherently adaptive artform. Dr Christopher Hogg is Senior Lecturer in Television Theory at the University of Westminster, UK. Chris specialises in television drama and television acting, with a particular interest in bringing together industry and academic perspectives. He is the co-author (with Dr Tom Cantrell, the University of York) of the book Acting in British Television (Palgrave Macmillan, 2017), and the co-editor (also with Cantrell) of the collection Exploring Television Acting (2018). .